2017
DOI: 10.1002/2017gl074857
|View full text |Cite
|
Sign up to set email alerts
|

The spatial extent of rainfall events and its relation to precipitation scaling

Abstract: Observations show that subdaily precipitation extremes increase with dew point temperature at a rate exceeding the Clausius‐Clapeyron (CC) relation. The understanding of this so‐called super CC scaling is still incomplete, and observations of convective cell properties could provide important information. Here the size and intensity of rain cells are investigated by using a tracking of rainfall events in high‐resolution radar data. Higher intensities are accompanied by larger rainfall areas. However, whereas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 36 publications
7
95
2
Order By: Relevance
“…Here we include finer details of convective rain cells and are able to sample a more continuous spectrum of the their size in the range from around 12 to 18 °C dew point temperature. Given this, we find that intensity and size of rain cells jointly increase under warming atmospheric conditions which is in line with the results of Lochbihler et al () and Lenderink et al ().…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here we include finer details of convective rain cells and are able to sample a more continuous spectrum of the their size in the range from around 12 to 18 °C dew point temperature. Given this, we find that intensity and size of rain cells jointly increase under warming atmospheric conditions which is in line with the results of Lochbihler et al () and Lenderink et al ().…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…So all of these studies point at a redistribution of rain intensity toward the center of the convective cell at the expense of the spatial extent. However, in contrast to these findings, Lochbihler et al (2017) find that convective cells grow in size at higher dew point temperatures and that this growth accelerates beyond 17 to 18 • C dew point temperature. For the same region, Lenderink et al (2017) obtain from station records of hourly precipitation that rainfall events at higher dew point temperatures blanket more stations than at lower dew point temperatures.…”
Section: 1029/2018jd029954contrasting
confidence: 95%
“…Nevertheless, in the model, the total precipitable coverage remains practically unchanged with temperature change, as is also assumed in the two statistical methods. This case study finding might contradict the recent observational study of Lochbihler et al (2017), where Dutch radar precipitation data were used to conclude that on average the precipitable cells increase with increasing temperature and precipitation intensity, especially at higher dew point temperatures. On the other hand, Wasko et al (2016) found evidence that precipitation intensity in Australia increases with temperature, while the storm's spatial extent decreases, as a redistribution of moisture towards the center takes place at the cost of the outer region of the precipitable area.…”
Section: Futurecontrasting
confidence: 99%
“…Eggert et al (2015) found that convective precipitation dominates precipitation extremes in Germany at scales below 10 km and shorter than 45 min. Over the Netherlands, 90% of summertime convective events were <7 km in cell diameters, and peak precipitation intensities declined rapidly within 5 km from the storm center (Lochbihler et al, 2017). Yet, considerable uncertainties remain in radar-derived quantitative estimates of precipitation intensities at surface level (Berne & Krajewski, 2013).…”
Section: Introductionmentioning
confidence: 99%